PEER TEACHING AS AN ALTERNATIVE PROFESSIONAL DEVELOPMENT STRATEGY FOR ECONOMICS EDUCATION TEACHERS (International Journal of Innovative Technologies in Economy, 2024)
This paper examines research concerning peer teaching as an alternative professional development technique for economics teachers. Peer teaching is an instructional strategy to enhance teacher professional development inside educational institutions. Through peer teaching, teachers actively engage in the professional development process. This is a prevalent professional development method for teachers aimed at familiarizing them with the practical application of the curriculum. The research is qualitative and employs a conceptual methodology. This study aimed to investigate peer teaching as an alternative professional development approach for teachers in economics. Data were obtained from various academic databases, including Google Scholar and ResearchGate. The study employed a thematic analysis of pertinent and contemporary literature. The study's themes included a deeper understanding of pedagogic and subject matter, learning new ways to teach, promoting collaboration through mentoring, enhancing organizational skills for teachers, and career development of teachers. The study's results demonstrate that peer teaching provides teachers with professional development opportunities that may enhance subject comprehension, foster teamwork, and offer mentoring support for beginner teachers. Ultimately, peer teaching can significantly promote teachers' professional growth and, thus, improve their curricular practices. This article advocates for the implementation of peer teaching to improve teacher professional development and curriculum delivery.